Providing Clean Energy with Micro Hydro Power Plants (PLTMH) for Babakan Village, Banten - Akmal Dzaky Adhynata; Farros Fadhlillah; Muhammad Rizky Fatahillah; Jihan Azzahra Diovant; Foezy Imroatul Awaliyah; Christian Hendro Setiawan; Muhammad Azhar Nurbahtiar; Edy Susanto; Muhammad Ridwan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Electrical energy is a vital need to support daily life in various sectors such as industry, housing and government. In Indonesia, the majority of electrical energy is still produced from fossil fuel plants, which have significant environmental impacts and limited resources. Therefore, the development of renewable energy is crucial to reduce dependence on fossil fuels. One promising alternative is the Micro Hydro Power Plant (PLTMH), which uses flowing water to produce electrical energy. This research focuses on the implementation of MHP in Babakan Banten Village, Bogor Regency, an area with the potential for abundant water flow throughout the year. This project aims to provide a reliable electricity supply for communities, most of whom do not yet have access to electricity from the national grid. This study includes the process of planning, assembling and testing the MHP system using field data such as river water discharge, land elevation (head) and other technical specifications. The measurement results show that the PLTMH with a generator capacity of 2 kW is able to meet the electricity needs of 18 houses in Babakan Village, Banten. System testing shows good operational stability with optimal turbine rotation at full load and results in accordance with planning. It is hoped that the implementation of this PLTMH will not only increase accessibility to sustainable electrical energy, but will also have a positive impact on the welfare of local communities. Utilization of locally available natural resources not only reduces dependence on conventional energy, but also becomes a real example of the application of technology for sustainable development in remote areas of Indonesia.